2020
DOI: 10.2147/copd.s232863
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impacts of Different Spirometry Reference Equations and Diagnostic Criteria on the Frequency of Airway Obstruction in Adult People of North China</p>

Abstract: Background and Objective: The reference equations and diagnostic criteria play a critical role in the interpretation of pulmonary function tests (PFTs). The aim was to investigate the impacts of different reference equations and diagnostic criteria on the frequency of airway obstruction in adult people of a large teaching hospital of North China. Methods: The spirometry data of all adult people who underwent PFTs in Qilu hospital from April 2012 to November 2015 were collected. Two spirometry reference equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The need of more precise LF calculations considering more aspects arose as published by Quanjer et al in 2012. Diagnostic thresholds must account for age-and gender-related changes for LF [20,21]. Potential misidentification of respiratory disease, especially in aging populations is a major public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…The need of more precise LF calculations considering more aspects arose as published by Quanjer et al in 2012. Diagnostic thresholds must account for age-and gender-related changes for LF [20,21]. Potential misidentification of respiratory disease, especially in aging populations is a major public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…A total of up to 11.4% (126/535) patients undergoing lung surgeries were spirometrically diagnosed as AFL using the fixed ratio (FEV 1 /FVC <70%) though preoperative spirometry and the incidence were in accordance with previous studies. 3,4,6,19 Generally, elderly males with higher levels of tobacco exposure tended to suffer from AFL. Our study confirmed that asymptomatic patients with AFL were at higher risk of PPCs than the general population in those who had undergone lung surgeries, accompanied by an GOLD guidelines recommended the use of postbronchodilator spirometry test and the fixed ratio as cutoff point (instead of lower limit of normal (LLN)) to confirm the presence of persistent airflow limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has shown that the incidence of newly diagnosed AFL is far more higher than expected. [3][4][5][6][7] Additionally, GOLD (Global Initiative for Chronic Obstructive Lung Disease) guidelines have indicated that never smokers with chronic airflow limitation may have no increased risk of lung cancer or cardiovascular comorbidities. 1,4,8,9 Postoperative pulmonary complications (PPCs), whose majority are postoperative pneumonia (POP) and respiratory failure, are common and frequently life-threatening in patients who have undergone lung surgeries, [10][11][12][13] with an incidence ranging from 9% to 40% due to the lack of recognized definitions.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ventilation and/or diffusion dysfunction are diagnosed with abnormal pulmonary function. A ventilation dysfunction can be obstructive (FEV1/FVC <92% of the predicted value (pred)) 38 or restrictive (TLC <80% pred, and for patients who did not have TLC records, FVC < LLN or <80% of pred accompany with FEV1/FVC ≥92% pred 39 , 40 ). Patients with two of the three indicators in FEF50%, FEF75%, and FEF 25%–75% lower than the pred of 65% were diagnosed with small airway dysfunction.…”
Section: Methodsmentioning
confidence: 99%